Immunogenomic Profiling and Classification of Prostate Cancer Based on HIF-1 Signaling Pathway - Song, Jukun; Chen, Weiming; Zhu, Guohua; Wang, Wei; Sun, Fa; Zhu, Jianguo (Frontiers in Oncology, 2020)
A large body of evidence indicated that HIF-1 signaling pathway plays an important roles in development of cancer, and many studies have been documented to exploring the mechanism of prostate cancer under the hypoxia circumstances on the basis of transcriptome data. However, few works have uncovered the immunogenomic profiling and classification of prostate cancer based on HIF-1 signaling pathway that may help to identify the optimal subset of PCa patients responsive to immunotherapy/chemotherapy. Using the publicly four PCa datasets, the immunogenomic PCa subsets was classified based on profiling of the HIF-1 signaling pathway. Three PCa subtypes, named HIF-1 High (HIF-1_H), HIF-1 Medium (HIF-1_M), and HIF-1 Low (HIF-1_L), was identified. The functional enrichment was analyzed in each subtype. Several cancer-associated pathways and immune-related pathways were hyperactivated in the HIF-1_H subtypes. In contrast, HIF-1_L subtypes were enriched in cell cycle and cell repair. Compared with other subtypes, HIF-1_H subtypes has greater immune cell infiltration and anti-tumor immune activity, and better survival prognosis. The submap and TIDE algorithm were used to predict the clinical response to immune checkpoint blockade, and GDSC was employed to screen chemotherapeutic targets for the potential treatment of PCa. Several chemotherapy drugs were identified in the GDSC dataset, including ABT 888, Temsirolimus, and EHT 1864. Meanwhile, HIF-1_H is defined as early PCa, and is more likely to respond to immunotherapy. The identification of immunogenomic PCa subtypes based on HIF-1 signaling pathway has potential clinical implications for PCa treatment. In addition, we found that immunopositive PCa subtypes will help to explore the reasons for the poor effect of PCa on immunotherapy, and it is expected that immunotherapy will be used to guide the personalized mangement and treatment of PCa patients.